Shippers vs. freight forwarders: Do they differ in their port choice decisions? Evidence from the Spanish ceramic tile industry. (November 2022) - Feo-Valero, María; Martínez-Moya, Julián
Abstract: The present research aims to compare shippers' and freight forwarders' port choice criteria in order to identify the main differences between these two decision-makers. Specifically, the research focuses on the port choice of the shippers belonging to the Spanish ceramic tile industry and the freight forwarders who manage their shipments. To do so, a mixed logit model is used with data obtained through a stated preference experiment. According to our results, shippers and freight forwarders differ only in the valuation of the cost attribute, with the latter being more cost-sensitive. Moreover, results indicate that freight forwarders are more conservative in their port choice decisions, as they show greater inertia in terms of continuing to use their current departure port. Furthermore, the policy scenario considered yields interesting conclusions about the effectiveness of the different potential actions that could be carried out by Port Authorities to attract cargo. Highlights: We compare shippers' and freight forwarders' port choice criteria. An application to land decision-makers belonging to Spanish ceramic tile industry. We use mixed logit model with data obtained through stated preference experiment. Results show freight forwarders as more cost-sensitive agent than shippers. The freight forwarders present greater inertia in terms of continuing to use their current port.